Determinants of students perceived manmade environmental hazards and risks in tertiary educational institutions - O. Daramola; O. Odunsi (Global Journal of Environmental Science and Management)
Environmental hazards caused by living conditions and human behaviour in residential areas are types of manmade hazards which have rarely been studied and documented in literature. Available studies that had considered theconventional residential environment had proved that residents’ perception were influenced by human and environmental factors. With focus on educational institutions, this paper assessed the determinants of students’ perception of environmental hazards and risks on campus environment. Using probability sampling technique, data were obtained through administration of questionnaire on 367 students of university, polytechnic and college of education in Oyo State. The data collected were analysed using inferential statistics. Findings revealed three broad factors which are socioeconomic background, sanitation behaviour and availability of environmental amenities. It was concluded that environmental amenities influenced students’ perception of environmental hazards and risks the most with a regression coefficient (β) of -0.373 compared with sanitation behaviour (β = 0.311) and socioeconomic background (β = 0.123). The appropriate authorities could therefore improve on maintenance of existing environmental amenities and/or provision of new ones in the educational institutions.